2016
DOI: 10.1038/leu.2016.160
|View full text |Cite
|
Sign up to set email alerts
|

Ordering of mutations in acute myeloid leukemia with partial tandem duplication of MLL (MLL-PTD)

Abstract: Partial tandem-duplication of MLL (MLL-PTD) characterizes acute myeloid leukemia (AML) patients often with a poor prognosis. To understand the order of occurrence of MLL-PTD in relation to other major AML mutations and to identify novel mutations that may be present in this unique AML molecular subtype, exome and targeted sequencing was performed on 85 MLL-PTD AML samples using HiSeq-2000. Genes involved in the cohesin complex (STAG2), a splicing factor (U2AF1) and a poorly studied gene, MGA were recurrently m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
76
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 41 publications
14
76
0
Order By: Relevance
“…Similar results were reported in a second publication [26], but this study also found that the combination of cohesin mutations with alterations in tyrosine kinases conferred a greater risk of relapse in patients with an otherwise “favorable” prognosis [26]. Lastly, recent studies have found that 26% of patients with MLL-PTD leukemia harbor cohesin mutations [27], but additional translocations have not been definitively studied thus far. Whether cohesin mutations cooperate or antagonize other common AML translocations remains unknown.…”
Section: Cohesin Mutations In Myeloid Neoplasmssupporting
confidence: 84%
“…Similar results were reported in a second publication [26], but this study also found that the combination of cohesin mutations with alterations in tyrosine kinases conferred a greater risk of relapse in patients with an otherwise “favorable” prognosis [26]. Lastly, recent studies have found that 26% of patients with MLL-PTD leukemia harbor cohesin mutations [27], but additional translocations have not been definitively studied thus far. Whether cohesin mutations cooperate or antagonize other common AML translocations remains unknown.…”
Section: Cohesin Mutations In Myeloid Neoplasmssupporting
confidence: 84%
“…Recently, several groups of researchers, including ourselves, uncovered the persistence of preleukemic clone at remission in adult AML, by showing the retention of canonical AML mutations with high VAF in remission samples (10,46-48). However, this scenario seems unlikely to be the case in pediatric ALL as our NGS data suggest that none of the somatic mutations persisted in matched remission samples (except for 2 cases with germline TP53 mutations and one case with a CREBBP stop-gain mutation that persisted in remission, which is likely also a germline mutation).…”
Section: Discussionmentioning
confidence: 99%
“…Illumina paired-end reads were aligned to NCBI build 37 using Novoalign, and somatic variants were called using Mutect (for single nucleotide variants, SNVs, LOD ≥ 6.3), VarScan (for SNVs and Indels, mutant supported by at least 6 reads, min-coverage ≥10, somatic-p-value ≤0.07, min-tumor-variant-freq ≥0.10, normal-variant-freq ≤0.05) and Pindel [for Indels, only indels that were less than 60bp long were retained (except for FLT3 , all the candidate mutations of FLT3 gene were retained for further analysis of potential internal tandem duplication (ITD) event), mutant supported by at least 6 reads and at least a 5% VAF]. For FLT3 -ITD detection, the Bam files were further analyzed using Pindel as described previously (10). All the candidate mutations were filtered with dbSNP131 [latest versions of the dbSNP database were not utilized as it contains some well characterized cancer mutations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently under discussion whether cytoreduction upon HU therapy selects for TP53* mutated cells. A recent study analyzed the impact of TP53* in MPN patients and, although it is common that at least one somatic TP53* allele is transcribed in patient cells, the authors did not find a direct association between TP53 inactivation and HU resistance or blast transformation [33]. TP53 can also interact with STAT3 and STAT5 [39,40] and it induces mRNA expression of STAT5A , but not of STAT5B [41].…”
Section: Targets In Mpn and Driver Mutationsmentioning
confidence: 99%